2013
DOI: 10.1016/j.toxlet.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anthocyanins on the AhR–CYP1A1 signaling pathway in human hepatocytes and human cancer cell lines

Abstract: Anthocyanins are plant pigments occurring in flowers and berry fruits. Since a phenomenon of food-drug interactions is increasingly emerging, we examined the effects of 21 major anthocyanins and the extracts from 3 food supplements containing anthocyanins on the aryl hydrocarbon receptor (AhR) – cytochrome P450 CYP1A1 signaling pathway in human hepatocytes and human hepatic HepG2 and intestinal LS174T cancer cells. Pelargonidin-3-O-rutinoside (PEL-2) and cyanidin-3,5-O-diglucoside (CYA-3) dose-dependently acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…This suggests that the mode of action of TCDD on cell proliferation and death differs from that of gemcitabine. TCDD has been demonstrated to activate AHR signaling and thereby regulate the expression of diverse molecules ( 1 - 4 ). The combination of TCDD and gemcitabine may exert a potent antitumor effect, suggesting a novel strategy for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the mode of action of TCDD on cell proliferation and death differs from that of gemcitabine. TCDD has been demonstrated to activate AHR signaling and thereby regulate the expression of diverse molecules ( 1 - 4 ). The combination of TCDD and gemcitabine may exert a potent antitumor effect, suggesting a novel strategy for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, bilberry-derived C3G was able to inhibit intestinal adenoma formation in an Apc (Min) mouse model (14). Previous preclinical studies have also detected the antitumor efficacy of C3G and P3G (7,(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 93%
“…C3G derived from bilberry also inhibited intestinal adenoma formation in an Apc(Min) mouse model (20). The present study was performed based on the antitumor efficacy potential of C3G and P3G observed in preclinical studies (9)(10)(11)13,14,(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…P3G and C3G are anthocyanin pigments extracted from black rice (10). P3G and C3G possess anti-cancer properties and have been used as medicine or as supplements for numerous decades (11)(12)(13)(14)(15)(16). P3G and C3G inhibit phospho-HER2 and phospho-AKT and were confirmed to induce HER2-positive breast cancer cell apoptosis in vitro (9).…”
Section: Introductionmentioning
confidence: 99%